PROSPEK PENDIDIKAN DALAM ERA TINGGAL LANDAS - Sulismadi, Sulismadi (Jurnal Bestari, 1993)
Indonesi next 21 th century will face three big problems i.e. science and technology development, ecology and emography. These problems will caouse Indonesian toward complicated position unless they increase and improve the quality of education. University is one of the  formal high education which must develop the human resources in order to be able to solve the problems. Indonesian always hopes that university can produce sklilful scholars who are able to advance the nation welfare.